2020
DOI: 10.3390/w12061596
|View full text |Cite
|
Sign up to set email alerts
|

Water Use and Soil Moisture Relationships on Western Juniper Trees at Different Growth Stages

Abstract: An enhanced understanding of plant water uptake is critical for making better-informed management decisions involving vegetative manipulation practices aimed to improve site productivity. This is particularly true in arid and semiarid locations where water is a scarce, yet precious commodity. In this project, we evaluated the interannual and seasonal variability of soil moisture and transpiration in sapling, juvenile, and mature western juniper (Juniperus occidentalis) trees in a semiarid rangeland ecosystem o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 89 publications
(108 reference statements)
0
15
0
Order By: Relevance
“…Deep percolation (DP) below the root zone, calculated by using the WBM, and shallow aquifer recharge (Re GW ), estimated by using the WTFM, occurred during the wet season (winter-spring). Re GW rates tended to decrease as juniper transpiration increased (based on data described by Abdallah et al [33]); however, some interannual variability was shown. Seasonal variations in precipitation resulted in variations in DP and Re GW , even during years when total precipitation amounts are similar.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Deep percolation (DP) below the root zone, calculated by using the WBM, and shallow aquifer recharge (Re GW ), estimated by using the WTFM, occurred during the wet season (winter-spring). Re GW rates tended to decrease as juniper transpiration increased (based on data described by Abdallah et al [33]); however, some interannual variability was shown. Seasonal variations in precipitation resulted in variations in DP and Re GW , even during years when total precipitation amounts are similar.…”
Section: Discussionmentioning
confidence: 90%
“…Mollnau et al [32] found that mature western juniper stand transpiration rates at a site in Central Oregon were approximately 0.4 mm per day during summer months and that transpiration rates were largely associated with soil water content. Abdallah et al [33] found that peak transpiration rates of western juniper trees ranged from 73 to 115 L day −1 , varying with seasonal and annual precipitation and soil water content. Calculations of sagebrush transpiration are very limited.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies attempting to evaluate western juniper transpiration and soil moisture relationships at different tree growth stages. They were reported that soil moisture decreases with increasing plantation age, and the soil dries seriously after 12 years [ 17 , 18 , 19 ]. Thus, a balance between soil water supply and root uptake is critical to the sustainability of ecosystem health [ 20 ], especially in dry areas where water is scarce.…”
Section: Introductionmentioning
confidence: 99%